Taxation and Corporate Risk-Taking - Dominika Langenmayr; Rebecca Lester (Center for Economic Studies and ifo Institute (CESifo), 2017)
We study whether the corporate tax system provides incentives for risky firm investment. We analytically and empirically show two main findings: first, risk-taking is positively related to the length of tax loss periods because the loss rules shift some risk to the government; and second, the tax rate has a positive effect on risk-taking for firms that expect to use losses, and a weak negative effect for those that cannot. Thus, the sign of the tax effect on risky investment hinges on firm-specific expectations of future loss recovery.
Keywords: H25; H32; G32; 330; corporate taxation; risk-taking; net operating losses